RANCANG BANGUN ALAT PENDETEKSI TERJADINYA BANJIR BERBASIS MIKROKONTROLLER MENGGUNAKAN SENSOR ULTRASONIC SR04 - Rohmat Nur Ibrahim; Komarudin Komarudin (STMIK Mardira Indonesia, Bandung, 2021)
The weakness of the management and supervision system for places where floods often occur is the trigger for the many losses experienced by the community. If you look at what the government did after the disaster occurred, the government only provided assistance and unsustainable countermeasures. A flood detection device based on a microcontroller has been made, in general this flood detection tool is designed using an ATMega 8535 microcontroller, sr04 Ultrasonic Sensor, Buzzer, Keypad, and 2x16 LCD. Through the Keypad we input the distance detected by the sensor and if the distance of the flood hazard is detected then the height is displayed via the LCD and then the buzzer makes a sound as a warning of a flood. This tool provides an early warning of the occurrence of flooding to residents to deal with flooding in order to avoid greater losses.Keywords: ATMega 8535, Sensor Ultrasonic sr04, Buzzer, Keypad, LCD 2x16.DOI : http://doi.org/10.5281/zenodo.5003733